Mahar Seperangkat Alat Shalat: Tradisi atau Simbol Komitmen Ketuhanan dan Tanggung Jawab - Makin; Farkhani (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
The tradition of giving a prayer set (seperangkat alat shalat) as a dowry has become a deeply embedded practice within Indonesian Muslim marriage culture. This study critically examines whether the prayer set functions merely as a cultural ritual or as a genuine symbol of divine commitment and spiritual responsibility. Employing a qualitative approach through in-depth interviews, participant observation, and document analysis conducted at the Office of Religious Affairs (KUA) in Musuk District, Boyolali, this study investigates the perceptions and religious practices of both givers and receivers of such dowries. The findings reveal a significant gap between the symbolic meaning of the dowry and its practical implementation in daily worship. While many perceive the dowry as a sacred token of faith, few translate this symbolism into consistent religious observance. This disconnect is influenced by socio-cultural environments, educational backgrounds, and the level of religious understanding among individuals. The study concludes that strengthening religious education and community engagement is crucial to transforming this tradition from a superficial ritual into a means of deepening spiritual consciousness within marital life. Consequently, the symbolic dowry of a prayer set should be viewed not only as a cultural inheritance but also as a catalyst for sustaining religious devotion and moral integrity in Muslim families.